Psoriasis and Cardiovascular Risk: Assessment by CUORE Project Risk Score in Italian Patients - Spyridoula Doukaki; Valentina Caputo; Maria Rita Bongiorno (Dermatology Research and Practice)
Background. Psoriasis is a common inflammatory and immune-mediated skin disease. There is growing controversy as to whether cardiovascular risk is elevated in psoriasis. A number of studies suggest a high prevalence of cardiovascular risk factors as well as cardiovascular diseases in psoriasis patients. Objective. The objective of this study was to estimate cardiovascular risk score in psoriasis patients and the relation between cardiovascular risk and psoriasis features. Cardiovascular risk was assessed by CUORE project risk score built within the longitudinal study of the Italian CUORE project and suited to populations with a low rate of coronary heart disease. Results. A case-control study in 210 psoriasis outpatients and 111 controls with skin diseases other than psoriasis was performed. CUORE project risk score was higher in patients than controls ( versus , ). Compared to controls, psoriasis patients have higher risk of developing major cardiovascular events. Cardiovascular risk was not related to psoriasis characteristics. Conclusion. Increased focus on identifying cardiovascular risk factors and initiation of preventive lifestyle changes or therapeutic interventions in patients with psoriasis is warranted.